ASSESSMENT ON SUITABILITY OF NORMALIZING AND PROBABILITY TYPE BENTHIC INDICES FOR PREDICTION OF BEHAVIOR OF INLAND WATER BODY - Gautam, Gayatri (International Journal of Research -GRANTHAALAYAH, 2015)
Natural variability in diversity of benthic macro invertebrate fauna or benthos has become a valuable tool in assessing, modeling and monitoring of water quality of inland water body with respect to its portability and of pollution level. However, inappropriate use of these indices may leads to false interpretation or prediction of behavior of inland water body. In this study we have employed two normalizing (i.e Shannon-Wiener Index (H’), Pielou´s Evenness (J’)) and one probability type (HurlbertPIE Index(PIE)) indices to evaluate behavior of Baikona tank water body between Jan-2008 to Dec 2009.Sampling was carried out for period of 24 months at three different location and diversity of benthos for each location was tabulated. It is observed that monthly variation these indices show same trend during observation period. Coefficient of correlation among normalizing indices is observed lesser degree when compared to correlation between normalizing and probability type index. Degree of correlation is equitable when samples in all three sampling stations are mapped as single for each sampling period. It can be summarized that to model the tank behavior (i)both normalizing type and probabilistic type indices to be considered.(ii)all samples taken at a time at different locations are to be mapped as single sample.